195 THE IMPACT OF COVID-19 RESTRICTIONS ON PATIENTS ATTENDING A FALLS ASSESSMENT SERVICE. (25th October 2022) - Pierpoint, R; Keating, J; McElwaine, P
Abstract: Background: Covid-19 impacted older peoples' confidence and mobility. Restrictions from March 2020 on our cohort of patients (> 65 years) reduced movement and social interactions leading to deconditioning and brain health implications. In our falls assessment service the clinical nurse specialist conducts a multifactorial assessment. We aimed to see if a difference existed in assessments of similar cohorts of patients' pre and post restrictions. Methods: A retrospective review of assessment measures for patients attending the falls service between October – December 2019 and 2021. Measures compared included gender, age, Fear-of-Falling (FOF), Timed Up and Go (TUG), Fracture Risk Assessment tool (FRAX), Vitamin D levels, grip strength and Body Mass Index (BMI). Results: Twenty-two patient charts were reviewed from 2019 and 2021. Both years had similar female and male patient data reviewed (14/22 female 2019, 15/22 female 2021). FOF was noted in 38% (8/21) of patients in 2019, versus 45% (10/22) in 2021. In 2021 the average age of our patient cohort had decreased by three years. The TUG average time increased by 2 seconds in 2021 (median time decreased by 2.5 seconds). The major osteoporotic average percentage decreased in 2021 by 1.1%, (median drop 9%), the hip fracture percentage decreased by 2.5% in 2021 (median drop 10.5%). The average vitamin D level decreased by 1mmol in 2021 (median decreased 54mmol), while BMI average increased by 2kg/m² (median increased by 6kg/m²). The average grip strength results in 2021 dropped by 11.5kg (median decreased by 10.5kg). Conclusion: Potential trends are observed in this data. We intend to examine a larger timeline/number of patients to be able to validate these findings, particularly FOF.